A fotografia como instrumento da documentação e preservação da memória: arte e sobrevivência no alto Vale do Ribeira - Lima, Manoel Roberto Nascimento de (2007)
The main aim of the present research is to base the photography as an instrument of historical and cultural reconstruction of the production of utilitarian of ceramic in the Alto Vale do Ribeira (State of São Paulo), one of the last areas to produce ceramic in traditional way, without the use of lathe. Such handicraft constitutes the corpus of this paper. This work try to reveal how, under that pressure, the ceramists' repertoire was deeply altered. Theoretically, the task mobilizes a group of works on the history of photography and on memory issues, as those signed by Boris Kossoy, Jorge Pedro Souza, Susan Sontag, Roland Barthes. Methodologically, it is an exhausting field research, complemented by a bibliographical research. The in loco investigation made possible the photographic registration of organizational forms of the communitarian work in three communities of Alto Vale do Ribeira and of the socioeconomic relationships of those groups. We believed we could appoint as result the woman's predominant role in the production and knowledge transmission processes, and the risk of extinction of the ceramic handcraft in those communities. Such possibility is aggravated by precariousness of the socioeconomic atmosphere in which the groups are inserted. In that aspect, the role of photography is of contributing not just for creation but also for attending the local social demand, avoiding the forgetfulness of the whole process of making ceramic still without use of lathe